Hemodynamic Significance of Middle Cerebral Artery Stenosis Associated With the Severity of Ipsilateral White Matter Changes - Fang, Hui; Leng, Xinyi; Pu, Yuehua; Zou, Xinying; Pan, Yuesong; Song, Bo; Soo, Yannie O. Y.; Leung, Thomas W. H.; Wang, Chunxue; Zhao, Xingquan; Wang, Yilong; Wang, Yongjun; et al. (Frontiers in Neurology, 2020)
Background: Previous studies conflicted in the association between intracranial atherosclerotic stenosis (ICAS) and the severity of white matter changes (WMC). Aims: We aimed to investigate the relationships between the severity of luminal stenosis and the hemodynamic significance of middle cerebral artery (MCA) stenosis, and the severity of ipsilateral WMC. Methods: In this cross-sectional study, patients with a recent ischemic stroke or transient ischemic attack and a 50-99% MCA-M1 stenosis in the Chinese Intracranial Atherosclerosis study cohort were analyzed. The post- to pre-stenotic signal intensity ratio (SIR) was obtained in time-of-flight MR angiography (MRA) to represent the hemodynamic significance of MCA-M1 stenosis, with a lower SIR indicating a hemodynamically more severe lesion. The severity of ipsilesional WMC was assessed by an age-related WMC (ARWMC) scale in T2-weighted fluid attenuated inversion recovery MR imaging. The relationships between the degree of MCA-M1 stenosis, SIR and ipsilesional ARWMC scale were analyzed. The MCA-M1 lesion with a higher percentage of stenosis was chosen for analyses in patients with bilateral MCA-M1 stenoses. Results: Among 180 subjects (mean age 64 years), a lower SIR of MCA-M1 stenosis (Spearman correlation coefficient, –0.543; p<0.001), but not the degree of stenosis (p=0.93), was significantly linearly correlated with a higher ipsilateral ARWMC. Multivariate ordinal logistic regression identified older age (OR=1.037; 95% CI, 1.008-1.066; p=0.011) and lower SIR (OR=0.010; 95%CI, 0.002-0.058; p<0.001) as independent predictors for more severe ipsilateral WMC. Conclusion: Patients with hemodynamically more severe ICAS are more likely to have more severe ipsilateral WMC. Longitudinal studies with sequential imaging exams may further reveal the impact of hemodynamic significant of ICAS on development and progression of WMC.